Combining data from high-energy p p -reactions and neutrinoless double-beta decay: Limits on the mass of the right-handed boson - Civitarese, Enrique Osvaldo (2016)
From the recently established lower-limits on the nonobservability of the neutrinoless double-beta decay of 76Ge (GERDA collaboration) and 136Xe (EXO-200 and KamLAND-Zen collaborations), combined with the ATLAS and CMS data, we extract limits for the left-right (LR) mixing angle, of the SU(2)L ×SU(2)R electroweak Hamiltonian. For the theoretical analysis, which is a model dependent, we have adopted a minimal extension of the Standard Model (SM) of Electroweak Interactions belonging to the SU(2)L ×SU(2)R representation. The nuclear-structure input of the analysis consists of a set of matrix elements and phase-space factors, and the experimental lower-limits for the half-lives. The other input are the ATLAS and CMS cross-section measurements of the pp-collisions into two-jets and two-leptons, performed at the large hadron collider (LHC). Our analysis yields the limit < 10-3 for MR > 3TeV, by combining the model-dependent limits extracted from the double-beta-decay measurements and those extracted from the results of the CMS and ATLAS measurements.